Updating the distribution and habitat pattern of Maurolicus stehmanni (Sternoptychidae, Stomiformes) in the Southwest Atlantic Ocean - Belleggia, Mauro (2018)
We updated the distribution and habitat patterns of Maurolicus stehmanni in the Southwest Atlantic Ocean by compiling data obtained from research surveys conducted on the Argentinean continental shelf, as well as from opportunistic records. This paper confirms the presence of M. stehmanni in the Argentinean continental shelf, extending its southernmost distributional limit by ca. 1000 km (from 43.0°S to 52.2°S). Adult specimens of M. stehmanni were collected in various locations from 2004 to 2016. Eggs and larvae of Maurolicus spp. were caught during ichthyoplankton tows carried out from 2003 to 2013. The present paper furthermore extends the habitat type in which this species was recorded: specimens were found in the inner continental shelf (between 46.2°S and 52.2°S) instead of the shelf break and continental slope. Two specimens were found lying dead upon the beach of Puerto Madryn, Nuevo Gulf (42.8°S). The presence of eggs and larvae in coastal embayments (San Matías and San José gulfs), in concomitant occurrence with adults, may suggest the establishment of this species in the region.